The GeoLink knowledge graph. Issue 2 (3rd April 2018) - Cheatham, Michelle; Krisnadhi, Adila; Amini, Reihaneh; Hitzler, Pascal; Janowicz, Krzysztof; Shepherd, Adam; Narock, Tom; Jones, Matt; Ji, Peng
ABSTRACT: GeoLink has leveraged linked data principles to create a dataset that allows users to seamlessly query and reason over some of the most prominent geoscience metadata repositories in the United States. The GeoLink dataset includes such diverse information as port calls made by oceanographic cruises, physical sample metadata, research project funding and staffing, and authorship of technical reports. The data has been published according to best practices for linked data and is publicly available via a SPARQL Protocol and RDF Query Language (SPARQL) end point that at present contains more than 45 million Resource Description Framework (RDF) triples together with a collection of ontologies and geo-visualization tools. This article describes the geoscience datasets, the modeling and publication process, and current uses of the dataset. The focus is on providing enough detail to enable researchers, application developers and others who wish to leverage the GeoLink data in their own work to do so. The dataset is available athttp://hdl.handle.net/1912/9524 .